Optimization Design of the Bucket Lifting Mechanism of Meal and Kitchen Truck based on Genetic Algorithm - Wang Zhongchang (Jixie chuandong)
Taking the bucket lifting mechanism of meal and kitchen truck of a company as research target,the mechanical and hydraulic integration virtual prototype model of bucket lifting mechanism of the meal and kitchen truck is built by the multi-body dynamics software ADAMS. The four geometric design points coordinate is parameterized and the articulated points of bucket lifting mechanism are optimized by multi island genetic algorithm in the optimization software i SIGHT,with the bucket lifting mechanism hydraulic cylinder maximum driving force minimum as the optimization target. Through the comparison of the original design data and the optimization results,the hydraulic cylinder maximum driving force is 8. 51% lower than before optimization of bucket lifting mechanism and the lifting arm maximum lifting force to rod is 5. 98% lower than before optimization in the working process,which has certain reference significance for the design and research of bucket lifting mechanism.